2020
DOI: 10.3390/jcm9051298
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Total Knee Replacement from Symptomology and Radiographic Structural Change Using Artificial Neural Networks—Data from the Osteoarthritis Initiative (OAI)

Abstract: The aim of the study was to longitudinally investigate symptomatic and structural factors prior to total knee replacement (TKR) surgery in order to identify influential factors that can predict a patient’s need for TKR surgery. In total, 165 participants (60% females; 64.5 ± 8.4 years; 29.7 ± 4.7 kg/m2) receiving a TKR in any of both knees within a four-year period were analyzed. Radiographic change, knee pain, knee function and quality of life were annually assessed prior to the TKR procedure. Self-learning a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 33 publications
1
19
1
Order By: Relevance
“…A strength of our study is the inclusion of a predictive model that could potentially be integrated into the electronic health record (EHR) to streamline the triage process for knee OA patients. In a similar study, Heisinger et al 21 used artificial neural networks to identify symptomatic and structural predictors of a patient's need for TKA surgery. The researchers found that structural changes to the knee documented via KL grade worsened significantly at every annual visit 4 years prior to the TKA procedure.…”
Section: Discussionmentioning
confidence: 99%
“…A strength of our study is the inclusion of a predictive model that could potentially be integrated into the electronic health record (EHR) to streamline the triage process for knee OA patients. In a similar study, Heisinger et al 21 used artificial neural networks to identify symptomatic and structural predictors of a patient's need for TKA surgery. The researchers found that structural changes to the knee documented via KL grade worsened significantly at every annual visit 4 years prior to the TKA procedure.…”
Section: Discussionmentioning
confidence: 99%
“… OA diagnosis and TKA need El-Galaly, A. 2020 Clinical Orthopaedics and Related Research [ 12 ] Heisinger, S. 2020 Journal of Clinical Medicine [ 13 ] Jafarzadeh, S. 2020 Osteoarthritis Cartilage [ 14 ] Leung, K. 2020 Radiology [ 15 ] Tolpadi, A.A. 2020 Scientific Reports [ 16 ] Yi, P. H. 2020 Knee [ 17 ] Norman, B. 2019 Journal of Digital Imaging [ 18 ] Tiulpin, A.…”
Section: Resultsmentioning
confidence: 99%
“… The provision of probability distributions for each KL grade prediction may assist clinicians in choosing KL grade in ambiguous cases. Heisinger (2020) [ 13 ] Journal of Clinical Medicine Need for TKA Artificial neural networks (ANNs) with linear, radial basis function and three-layer perceptron neural networks architectures Total percentage of correctly predicted knees: 80%. Positive predictive value: 84%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there have been no comprehensive attempts to identify the most important features and to build a survival‐based model for predicting the time to TKR for an individual with OA. Recently, Heisinger et al, with the use of a small cohort (n = 165), applied 14 factors in a 4‐year period prior to TKR to predict an individual’s need for TKR surgery (11). In addition, an image‐based model with knee radiographs to classify individuals with OA who are at high risk of TKR has also been recently developed (12).…”
Section: Introductionmentioning
confidence: 99%